2000
DOI: 10.1021/cm990238q
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Crystal and Electronic Structures of Three 2:1 Salts of the Organic Donor Molecule BEDT-TTF with Pentafluorothiomethylsulfonate Anions SF5CH2SO3-, SF5CHFSO3-, and SF5CF2SO3-

Abstract: Salts of the donor molecule, bis(ethylenedithio)tetrathiafulvalene (BEDT-TTF or ET), with pentafluorothiomethylsulfonate (SF 5 CX 2 SO 3 -, X ) H or F) anions have been prepared. Three phases, β′′-(ET) 2 SF 5 CH 2 SO 3 , β′-(ET) 2 SF 5 CF 2 SO 3 , and β′′-(ET) 2 SF 5 CHFSO 3 were obtained by electrocrystallization with the corresponding LiSF 5 CX 2 SO 3 electrolytes. The structures of these salts were determined by single-crystal X-ray diffraction, and their physical properties were examined by electrical resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
51
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 47 publications
10
51
0
Order By: Relevance
“…There is controversy about whether nuclear magnetic resonance measurements can distinguish these two charge orderings. 64 The charge distribution observed 14 for ␤Љ-(BEDT-TTF) 2 SF 5 CH 2 SO 3 is consistent with charge ordering considered here.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…There is controversy about whether nuclear magnetic resonance measurements can distinguish these two charge orderings. 64 The charge distribution observed 14 for ␤Љ-(BEDT-TTF) 2 SF 5 CH 2 SO 3 is consistent with charge ordering considered here.…”
Section: Discussionsupporting
confidence: 83%
“…Band structure calculations 14,17,27,30,31 predict that all these materials are metallic. Hence, the different phases must be due to electronic interactions.…”
Section: The Extended Hubbard Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The most significant feature in this X-ray crystal data is that the distance of the central C5@C6 bond (1.388 (16) Previous theoretical studies have suggested that the HOMO of BEDT-TTF (bis(ethylenedithio)tetrathiafulvalene) includes the central C@C bonding and immediate four C-S anti-bonding orbitals of BEDT-TTF. Both the lengthening of the central C@C bond distance and the lessening of the immediate C-S bond distances have previously been predicted, based on the removal of one electron from the HOMO, leading to the generation of the TTF cation radical [10,11]. The change in the bond distances of CET-EDTTTF upon the formation of the complex analogously indicates that the oxidation of the CET-EDTTTF unit takes place, resulting in the formation of the radical species with the spin density mostly residing on the central S 2 C@CS 2 p-system.…”
mentioning
confidence: 89%